Pengaruh Jam Belajar Dan Akses Internet Terhadap Indeks Prestasi Mahasiswa Kelas C Ekonomi Pembangunan Tahun 2021 - Melati Sinaga; Ristauli Siregar; Sintia Anggela; Ayu Doloksaribu; Indrawan Saputra; Stefanus Surbakti; Dicky Perwira Ompusunggu (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In educational institutions, learning performance is an important indicator for measuring the success of teaching learning. The goal of learning is the change in behavior that a person is expected to after a learning process. Factors that can affect the difference in learning outcomes of each student are internal and external factors. Internal factors are factors that exist in the individual who is studying. External factors are factors that exist outside the individual. Many things include internal and external factors, including long hours of study, environment and organization. The implementation of the learning process on campus cannot guarantee whether students can the IP as expected. The researchers therefore wanted to look at the impact of school hours, the environment, and the organization on the IP of Class C students in Development Economics. The research approach used by the author in this study is quantitative research. The total sample examined was 41 people based on the criteria that have been determined. The research uses the probability sampling technique, which is the method of Random Sampling. All members of the population are assumed to have equal opportunities to be selected as research samples.